A novel composite adaptive flap controller design by a high-efficient modified differential evolution identification approach. (May 2018) - Li, Nailu; Mu, Anle; Yang, Xiyun; Magar, Kaman T.; Liu, Chao
Abstract: The optimal tuning of adaptive flap controller can improve adaptive flap control performance on uncertain operating environments, but the optimization process is usually time-consuming and it is difficult to design proper optimal tuning strategy for the flap control system (FCS). To solve this problem, a novel adaptive flap controller is designed based on a high-efficient differential evolution (DE) identification technique and composite adaptive internal model control (CAIMC) strategy. The optimal tuning can be easily obtained by DE identified inverse of the FCS via CAIMC structure. To achieve fast tuning, a high-efficient modified adaptive DE algorithm is proposed with new mutant operator and varying range adaptive mechanism for the FCS identification. A tradeoff between optimized adaptive flap control and low computation cost is successfully achieved by proposed controller. Simulation results show the robustness of proposed method and its superiority to conventional adaptive IMC (AIMC) flap controller and the CAIMC flap controllers using other DE algorithms on various uncertain operating conditions. The high computation efficiency of proposed controller is also verified based on the computation time on those operating cases. Highlights: A novel adaptive flap controller based on Differential Evolution (DE) identification technique. Optimized adaptive flap control by DE based CAIMC strategy over conventional adaptive IMC strategy. Fast tuning of proposed controller by proposed high-efficient modified DE algorithm with varying range adaptive mechanism. Strong robustness and high computation efficiency of proposed controller on diverse uncertain operating conditions.